Chung's swing technique: a new technique for small-incision lenticule extraction. Issue 1 (December 2016) - Kim, Bu; Mun, Su; Lee, Dae; Choi, Hyun; Chung, Young
Abstract Background To introduce the Chung's swing technique for small-incision lenticule extraction (SMILE). Methods A total of 112 eyes of 56 patients were included in this study. Patients were divided into two groups: 52 eyes of 26 patients were treated with SMILE using a traditional method (traditional group) and 60 eyes of 30 patients were treated with SMILE using the Chung's swing technique (swing group). Results At 1 month postoperatively, all eyes in both groups had an uncorrected distance visual acuity of 20/20 or better. The efficacy indices were 1.09 ± 0.17 and 1.02 ± 0.11 (p  = 0.492), and the safety indices were 1.12 ± 0.14 and 1.09 ± 0.15 (p  = 0.537), for the traditional and swing group, respectively. All eyes in both groups underwent successful lenticule extraction; all lenticules were intact and complete. The mean lenticule extraction times were 48.67 ± 4.9 and 39.8 ± 5.53 s, for the traditional and swing group, respectively (p  < 0.001). Conclusions The Chung's swing technique is efficient for lenticule separation and extraction. Our study results showed good clinical outcomes. Trial registration Trial registration number:KCT0001978 . Registered 22 July 2016. Retrospectively registered.